Conventional chemotherapy for acute myeloid leukemia in older adults: Impact on nutritional, cognitive, and functional status. (27th March 2021) - Jouzier, Claire; Hamel, Jean‐François; Dumas, Pierre‐Yves; Delaunay, Jacques; Bonmati, Caroline; Guièze, Romain; Hunault, Mathilde; Banos, Anne; Lioure, Bruno; Béné, Marie‐Christine; Ianotto, Jean‐Christophe; Ojeda‐Uribe, Mario; et al.
Abstract: Objectives: The impact of conventional treatment for acute myeloid leukemia (AML) on the nutritional, cognitive, and functional status of elderly patients is seldom studied. This assessment was performed in the context of the LAMSA 2007 trial. Methods: The trial enrolled 424 patients with de novo AML. Among them, 316 benefited from geriatric assessment (GA) including nutritional, cognitive, and functional status and were scored according to Eastern Cooperative Oncology Group (ECOG) and sorror for the prediction of treatment toxicity, morbidity, and mortality. Patients were investigated at diagnosis for three times during follow‐up. Results: This study showed that AML and its treatment have no impact on cognitive ( P  = .554) nor functional status ( P  = .842 for Activity of Daily Living and P  = .087 for Instrumental Activities of Daily Living). The nutritional status improved over time ( P  = .041). None of these three parameters at baseline, associated or not with ECOG and sorror scores, impacted survivals or toxicities. Conclusions: The cognitive, functional, and nutritional status had no impact in this cohort of fit elderly AML patients without unfavorable cytogenetics. The GA tools used provided no additional information compared with ECOG and sorror scores, to predict toxicity, morbidity, or mortality due to intensive chemotherapy.